Thymus serpyllum Essential Oil and Its Biological Activity as a Modern Food Preserver - Galovičová, Lucia (Plants (Basel), 2021)
The aim of this study was to analyze the chemical composition and biological and antibiofilm activity of the essential oil (EO) of Thymus serpyllum with the use of a MALDI-TOF MS Biotyper. The main compounds of the EO were thymol, 18.8%; carvacrol, 17.4%; o-cymene, 15.4%; and geraniol, 10.7%. It was found that free-radical scavenging activity was high. The highest antimicrobial activity was observed against Pseudomonas aeruginosa, Salmonella enteritidis, and biofilm-forming bacteria. The changes in the biofilm structure after T. serpyllum EO application confirmed the inhibitory action and the most pronounced effect was observed on Bacillus subtilis biofilm. The antifungal activity of the vapor phase was the most effective against Penicillium crustosum. T. serpyllum should be a suitable alternative to synthetic antioxidants as well as antimicrobials. The EO of T. serpyllum can be used in the vapor phase in the storage of root vegetables as well as a growth inhibitor of Penicillium on bread.